Alterations Functional Connectivity in Temporal Lobe Epilepsy and Their Relationships With Cognitive Function: A Longitudinal Resting-State fMRI Study - Qin, Lu; Jiang, Wenyu; Zheng, Jinou; Zhou, Xia; Zhang, Zhao; Liu, Jinping (Frontiers in Neurology, 2020)
Background: Cognitive impairments in temporal lobe epilepsy (TLE) patients has been described as a chronically progressive feature of the disease. However, it remains largely unknown how severe recurrent seizures modify neuronal circuits in the human brain and subsequently degrade cognitive function. Here, we aimed to investigate longitudinal alterations by functional magnetic resonance imaging (fMRI) in TLE patients and to assess how those alterations are related to cognitive function performance. Methods: Sixteen TLE patients and twenty normal controls (NCs) were recruited for a study to observe longitudinal alterations in resting-state functional connectivity (FC) and estimate alertness, orientation, and executive function both at baseline and at a follow-up time approximately 3 years later. Results: TLE patients, compared with NCs, showed impaired executive function, intrinsic alertness, and phasic alertness and exhibited lengthened reaction time (RT) in the spatial cue and centre cue conditions at baseline. The orienting function of TLE patients was declined at follow-up compared to the baseline. Cross-sectional analysis demonstrated that TLE patients displayed significantly greater positive correlation than NCs between the right dorsolateral prefrontal cortex (DLPFC) and the right inferior parietal lobule (IPL) and right superior frontal gyrus (SFG). Furthermore, among TLE patients, the longitudinal study revealed a decrease in correlation between the right DLPFC and the right SFG compared to the baseline. In addition, there was a significant negative correlation between the longitudinal change in FC and the change in orienting function in TLE subjects. Conclusions: Abnormal connectivity between the DLPFC and the SFG suggests the potential of longitudinal resting-state fMRI to delineate regions relevant to cognitive dysfunction for disease progression.